Traumatic dental injuries among children attending the public after-hours emergency dental clinic in Bergen, Norway - Faiza D. Sælen; Jorma I. Virtanen; Marit S. Skeie; Gerhard Sulo; Dorina S. Thelen (Medical Journals Sweden, 2024)
Objectives: To investigate traumatic dental injuries (TDIs) among children who for 1 year attended a Norwegian public after-hours emergency public dental (EPD) clinic. Materials and methods: The study included 7-18-year-olds (n = 312) who presented at the EPD clinic, underwent a clinical dental examination, and consented to the disclosure of clinical information. Recording of TDIs was restricted to anterior permanent teeth. Potential TDI predictors were also analysed. Results: Almost half (n = 148) of the children were assessed with TDIs in permanent teeth, showing a mean age of 11.0 (standard deviation [SD]: 3.5) years. Males constituted 54.7%. The children experienced TDIs often outside school hours (43.9%), and the majority (58.1%) were caused by falls/accidents. Sixty of them experienced only one TDI. The most common location was the maxillary central incisors. Assessment of TDIs according to severity, could only be done in 131 individuals, involving 253 TDIs. Of these, 81.8% were mild. The odds of visiting the emergency clinic for a TDI were higher (odds ratio [OR] = 2.64, confidence interval [CI]: 1.61-4.31) among children with previous TDIs and lower (OR = 0.28, CI: 0.12-0.68) among those with poor dental attendance. Conclusions: Traumatic dental injuries were a common reason for seeking emergency care. Milder injuries dominated and involved mostly one maxillary central incisor. Previous episodes of TDIs and attendance patterns seemed to be associated with seeking care for TDIs.